The Effects of Immigration and Refugee Policies on Social Integration and Community - Chiku Ashura (Journal of Public Representative and Society Provision, 2021)
Integration and participation in local communities are studied as they relate to immigration and refugee policies. This article examines the effects of immigration and refugee policies on social integration and community. We used a combination of survey analysis and in-depth interviews to learn more about immigrant and refugee experiences in the US. Our research showed that a lack of social support networks, together with language obstacles and discrimination, were major factors preventing people from successfully integrating into society. However, it was shown that social support networks are crucial for effective integration and involvement. The consequences of our research for policymakers and practitioners are substantial. Policymakers and practitioners can aid in breaking down language barriers and fostering greater social integration and community cohesion by prioritizing funding for accessible and affordable language acquisition programs, interpretation and translation services, and programs that promote social support networks. Further, policymakers and practitioners can aid in the fight against racism and discrimination and advance a more welcoming and inclusive society by placing a premium on anti-discrimination measures, education, and awareness-raising. Successful social integration and community participation among immigrants and refugees is emphasized throughout this study by emphasizing the significance of addressing language obstacles, prejudice, and a lack of social support networks. Greater social integration and community cohesion for immigrants, refugees, and host communities can be fostered by implementing the policy and practice recommendations indicated in this study.